Antimicrobial stewardship: a qualitative study of the development of national guidelines for antibiotic use in hospitals - Eli Feiring; Anne Berit Walter (BMC, 2017)
Abstract Background As effective antibiotics are becoming a scarce resource, governmental regulation is needed to promote responsible use. Implementation of antibiotic stewardship and practice guidelines in health care facilities seems to be crucial to this effort. Empirical studies suggest, however, that guidelines have limited influence on health professionals' behavior and practice. Barriers and facilitators to guideline implementability are much studied, but little attention has been given to health professionals' perceptions of normative acceptability of guidelines as a condition for compliance. The aim of the present study was first, to examine if and how aspects potentially promoting acceptability and compliance among clinical target users were addressed during development of Norwegian national guidelines for antibiotic use in hospitals and second, to identify procedural characteristics of the development process that were perceived by target users to yield legitimate guidelines. Methods Qualitative deductive thematic analysis was used. A theoretical framework inspired by the AGREE II Instrument and the Accountability for reasonableness framework assisted data gathering and interpretation. Archival data was collected and used to detail the guideline development process. Semi-structured, in-depth interviews with eight clinicians with extensive knowledge of the guidelines were carried out. Results Guideline development was characterized by i) broad agreement about scope and purpose, ii) broad involvement of stakeholders in the development process, iii) use of systematic methods to search for and apply evidence, iv) easily identifiable and specific recommendations, v) provision of tools on how to put recommendations into practice, and vi) editorial independence. Several procedural characteristics were perceived by the interviewees as promoting guideline legitimacy; i) diverse perspectives systematically involved in the process, ii) accessibility and transparency of the rationales for decision making, iii) opportunities for appeals and reconsiderations, and iv) regulative authority. Conclusions This study provides insights as to how guidelines that are intended to promote responsible use of antibiotics in hospitals can be carefully developed to facilitate perceptions of relevance, transparency, and authority by health professionals.